Morbidity Patterns and Health Needs of the Geriatric patients in a Tertiary Care Hospital - Rabiah Mahwish, Muhammad Ali, Arham Hussain, Kanwal Manzoor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The aged population of the world is increasing. Old age is associated with increased risk of morbidity and mortality. This puts burden on health services, both financially and in terms of workload. Aim: To determine the morbidity patterns and health needs of this age group. Methods: A descriptive cross-sectional study was conducted among the geriatric patients presenting in the outdoor department of services hospital Lahore. The sample size was 220, calculated using the WHO statistical software S size. Nonprobability convenient sampling technique was used. The confidence interval was 95% and relative margin of error was 10%. Chi-square test was used to check the statistical significance. Results: Out of 220 study subjects, 13 had only 1 morbid condition and 137 were suffering from more than 3 morbidities. Hypertension was the most prevalent morbidity (65.9%), followed by eye cataract (61.18%). Other morbid conditions in descending order were diabetes mellitus (47.27%), osteoarthritis (43.63%), coronary heart disease (38.18%), obesity (35.45%), respiratory diseases (30.90%), hearing impairment (25%). Significant association of morbidities with body mass index was observed. Almost 37.7% of respondents reported feeling of loneliness. Most of the geriatric patients were involved in religious activities (88.2%). Spectacles (55%) were the most frequently used supporting aids followed by walking sticks (26.4%). Conclusion: A high proportion of geriatric patients have more than 3 morbidities with hypertension being the most common. Body mass index and smoking were significant risk factors. Geriatrics showed prevalent psychological problems.